Addressing multilevel barriers to clinical trial participation among Black and White men with prostate cancer through the PACCT study. (20th December 2022) - Eggly, Susan; Senft, Nicole; Kim, Seongho; Heath, Elisabeth I.; Jang, Hyejeong; Moore, Tanina F.; Baidoun, Fatmeh; Manning, Mark A.; Penner, Louis A.; Albrecht, Terrance L.; Carducci, Michael A.; Lansey, Dina; et al.
Abstract: Background: Cancer clinical trial participation is low and inequitable. Partnering Around Cancer Clinical Trials (PACCT) addressed systemic and interpersonal barriers through an observational study of eligibility and an intervention to improve patient–physician communication and trial invitation rates. Methods: Physicians at two comprehensive cancer centers and Black and White men with prostate cancer participated. Patients were followed for 2 years to determine whether they became potentially eligible for an available therapeutic trial. Potentially eligible patients were randomized to receive a trials‐focused Question Prompt List or usual care. Patient–physician interactions were video‐recorded. Outcomes included communication quality and trial invitation rates. Descriptive analyses assessed associations between sociodemographic characteristics and eligibility and effects of the intervention on outcomes. Results: Only 44 (22.1%) of participating patients ( n  = 199) became potentially eligible for an available clinical trial. Patients with higher incomes were more often eligible (>$80, 000 vs. <$40, 000, adjusted OR = 6.06 [SD, 1.97]; $40, 000–$79, 000 vs. <$40, 000, adjusted OR = 4.40 [SD, 1.81]). Among eligible patients randomized to the intervention ( n  = 19) or usual care ( n  = 25), Black patients randomized to the intervention reported participating more actively than usual care patients, while White intervention patients reported participating less actively (difference, 0.41 vs. −0.34). Intervention patients received more trial invitations than usual care patients (73.7% vs. 60.0%); this effect was greater for Black (80.0% vs. 30.0%) than White patients (80.0% vs. 66.7%). Conclusions: Findings suggest the greatest enrollment barrier is eligibility for an available trial, but a communication intervention can improve communication quality and trial invitation rates, especially for eligible Black patients. Abstract : This multisite study addressed two barriers to enrollment of Black and White men in prostate cancer clinical trials—patient eligibility and patient–physician communication. Findings showed eligibility, a systemic barrier, is the biggest barrier; but a simple Question Prompt List communication intervention can improve interpersonal barriers including communication quality and trial invitation rates, especially for Black patients.